Estrous cycle influences excitatory amino acid transport and visceral pain sensitivity in the rat: effects of early-life stress. Issue 1 (December 2016) - Moloney, Rachel; Sajjad, Jahangir; Foley, Tara; Felice, Valeria; Dinan, Timothy; Cryan, John; O'Mahony, Siobhain
Abstract Background Early-life stress (ELS) is a recognized risk factor for chronic pain disorders, and females appear to be more sensitive to the negative effects of stress. Moreover, estrous cycle-related fluctuations in estrogen levels have been linked with alternating pain sensitivity. Aberrant central circuitry involving both the anterior cingulate cortex (ACC) and the lumbosacral spinal cord has also been implicated in the modulation of visceral pain in clinical and preclinical studies. Here we further investigate changes in visceral pain sensitivity and central glutamatergic systems in rats with respect to estrous cycle and ELS. Methods We investigated visceral sensitivity in adult female Sprague-Dawley rats, which had undergone maternal separation (MS) in early life or remained non-separated (NS), by performing colorectal distension (CRD). We also assessed excitatory amino acid uptake through excitatory amino acid transporters (EAATs) in the lumbosacral spinal cord and ACC. Results NS animals in proestrus and estrus exhibited reduced EAAT uptake and decreased threshold to CRD. Moreover, total pain behaviors were increased in these stages. MS rats exhibited lower pain thresholds and higher total pain behaviors to CRD across all stages of the estrous cycle. Interestingly, cortical EAAT function in MS rats was inhibited in the low estrogen state—an effect completely opposite to that seen in NS rats. Conclusions This data confirms that estrous cycle and ELS are significant factors in visceral sensitivity and fluctuations in EAAT function may be a perpetuating factor mediating central sensitization.